Брендинг функциялары - Бекболатұлы, Ж. (Herald of Journalism, 2016)
В статье рассматривается история становления и развития брендинга. Изучаются актуальные вопросы науки, теории практики брендинга. Исследуются связи брендинга с такими науками, как психология, связи с общественностью, социология, дизайн, реклама. В статье даются определения функциям брендинга. Рассматриваются правовые, дифференциальные, коммерческие и творческие фнукции. Также автор останавливается на таких тенденциях берндинга, как прававая, рациональная и иррациональная. Даетсяопределение брендинга как отрасли науки.This article is considered the problems of theory of formation and development of brending. The topical questions of the science, theory and practice of brending are studied. It is researched connection of brending with a science such as psychology, connection with a public relations, sociology, design, advertising. It is given the definition to function of brending. It is studied legal, differencial, commercial a creative functions. Also, the autor makes on tendention of brending such as legal, rational and irrational. It is given a definition of brending as branch of science.